Human Capital, Radical Product Innovation, and Product Proliferation: Evidence from China. Issue 7 (28th May 2022) - Sun, Xiuli
ABSTRACT: This paper examines how firm-level human capital indicators influence product innovation using firm-level enterprise survey data from China conducted by the World Bank. The human capital indicators we use include the number of highly educated workers, the general manager's education and tenure, and the management team's education and age. We use the Logit, Negative Binomial, and linear Hurdle estimators to estimate the knowledge production function models that are augmented by our human capital variables. We find that human capital indicators have much more important effects in mid-sized cities than in metropolitan cities where R&D is the most important factor. Radical product innovation involves more human capital than product proliferation. Also, GM's tenure has a positive effect on product innovation in mid-sized cities, while it has a negative effect in metropolitan cities. After taking the endogeneity of human capital indicators into account, our results still hold. Finally, we also examine moderating effects of market instability and competition.